Neutrophil-Lymphocyte Ratio, Platelet-Lymphocyte Ratio, and Length of Cervix as Predictors of Premature Delivery during the Covid-19 Pandemic at Cipto Mangunkusumo General Hospital - Djusad, Suskhan; Surya, Ilham Utama; Purnadiputra, Akbar; Pribadi, Muhamad Ichsan; Wicaksono, Muhammad Adhitya (Indonesian Socety of Obstetrics and Gynecology, 2024)
Abstract Objective: The percentage of neonatal death continues to increase on a yearly basis, in which prematurity is the main cause of mortality. This study determines the descriptive outcomes between neutrophil-lymphocyte ratio (NLR), platelet lymphocyte ratio (PLT), and cervical length as predictors of preterm birth. Methods: A retrospective analytical study is conducted using medical records from Dr. Cipto Mangunkusumo National General Hospital. The subjects of this study includes pregnant women diagnosed with preterm delivery in Dr. Cipto Mangunkusumo National General Hospital from April 2020 to June 2021. Data on neutrophil-lymphocyte and platelet-lymphocyte ratios were obtained from a complete blood test during admission. Cervical length is measured using transvaginal ultrasound. The three variables are compared to the control group, which consists of pregnant women with full term delivery. Results: This study conducted a study with a total of 81 subjects with preterm delivery and 92 subjects with full term delivery. There were no significant difference in neutrophil-lymphocyte and platelet-lymphocyte ratios between preterm and a-term delivery (p=0.795 and p=0.475). Cervical length was significantly longer in preterm compared to full term delivery (24,50 vs 3,15 mm; p = 0,031). The neck cervical length of several participants was not assessed. Cervical length in preterm delivery obtained only 21 patients and data from 10 subjects from the full term group. Conclusion: The ratio of neutrophil-lymphocyte and platelet-lymphocyte cannot be used as predictors of preterm birth in all pregnant women. To reduce bias in this research, studies with prospective study design with a specified subject criteria are needed. Keywords: cervical length, neutrophil-lymphocyte ratio, platelet lymphocyte ratio, premature delivery